Applications of two novel computational music analysis systems: The General Chord Type and the Directional Interval Class - (:unkn) unknown (My University, 2019)
Η παρούσα εργασία πραγματεύεται εφαρμογές υπολογιστικών συστημάτων μουσικής ανάλυσης. Το «General Chord Type» (ή «GCT») και το «Directional Interval Class» (ή «DIC») είναι τα δύο μοντέλα που αναλύονται και αφορούν την αυτόματη μουσική ανάλυση και αναπαράσταση. Το GCT είναι ένα εργαλείο που πραγματοποιεί αρμονική ανάλυση, ενώ το DIC αναλύει τις αποστάσεις μεταξύ συγχορδιών. Και τα δύο εργαλεία, προτείνουν μια νέα σημειογραφία η οποία περιέχει σημαντικές αρμονικές πληροφορίες ενός κομματιού. Η εργασία προσεγγίζεται τεχνικά από την δημιουργία των αλγορίθμων οι οποίοι βασίζονται τα δύο μοντέλα, καθώς και από στατιστική ανάλυση και οπτικοποίηση των αποτελεσμάτων ως μέσα ταξινόμησης μουσικών κομματιών. Τα αποτελέσματα προκύπτουν από την εφαρμογή και των δύο εργαλείων σε ψηφιακές παρτιτούρες οι οποίες ανήκουν σε διαφορετικά είδη μουσικής. H οπτικοποίηση δεδομένων αποκαλύπτει τις αρμονικές ομοιότητες και διαφορές μεταξύ διαφορετικών μουσικών ειδών βασισμένες στα αποτελέσματα των δυο εργαλείων. Η μελέτη αποτελεί την πρώτη στατιστική και γραφική ανάλυση των δύο μοντέλων, στην οποία μπορούν να βασιστούν μελόντικες εφαρμογές αυτόματης μουσικής ανάλυσης και εναρμόνισης, αυτόματης μουσικής δημιουργίας και πληθώρα άλλων.

This dissertation addresses the question of how two novel representations of chords are implemented in well-studied datasets. The aforementioned models are reconstructed and analyzed using statistical methods. Through the use of this process music information retrieval and data visualization methods are applied to those tools for the first time. The aim of this study is to add to the range of implementations of these tools, as well as explore visualization methods that can prove useful for a range of case studies related to music perception, like music harmonization or automatic music generation. The first tool, the General Chord Type (abbreviated GCT), is a novel representation of chords, based on existing representation formats and music notation systems. It is a computer-understandable model that extracts and analyzes musical information, based on rules provided in a specific format by the user. It has the potential to become the basis for future implementations of music generation and genre classification systems. Here, it is used as a representation tool and as a basis for genre classification. The second tool proposed, the Directed Interval Class vector (abbreviated DIC) deals with the intervallic content between chords. It is a unique tool in two distinct ways: it requires the retrieval of a significantly smaller amount of information than any of the existing models and it can be used in exploring musical analysis methods as well as genre classification. Both of these tools are idiom-independent, in contrast to already existing models.
Keywords: Μουσική Πληροφορική, Μουσική Ανάλυση, Αυτόματη Μουσική Ανάλυση, Μουσικά Υπολογιστικά Συστήματα, Μέθοδοι Οπτικοποίησης Δεδομένων, Αυτόματη Ταξινόμηση Μουσιικής, Στατιστική Ανάλυση Δεδομένων, Αλγόριθμοι Μουσικής Ανάλυσης; Music Informatics, Musical Analysis, Automatic Musical Analysis, Music Computational Systems, Data Visualisation Methods, Automatic Music Classification, Data Statistical Analysis, Musical Analysis Algorithms